ASSESSMENTS AS REGARD OF SERVICE QUALITY OF TOURISTIC CONSUMERS WHO PARTICIPATE IN EQUESTRIAN TREKKING ACTIVITIES: AN APPLICATION IN CORE CAPPADOCIA, TURKEY - Burcu Gülsevil BELBER; Yakup ERDOĞAN (Geo Journal of Tourism and Geosites, 2019)
In this study, based on the Servqual Scale a questionnaire consisting of 4 sections and 48 questions was applied in order to determine the service quality evaluations of domestic and foreign tourist consumers participating in equestrian trekking activities in Nevşehir. The study was limited to the local and foreign tourists visiting the equestrian trekking enterprises in Nevşehir. The survey was carried out with 350 people and T test ANOVA and LSD analyses were conducted. The findings of the study showed that the average score of domestic and foreign tourist about physical properties is very close to each other and domestic tourists have positive but foreign tourists have negative evaluations on reliability. In terms of willingness, the evaluations of domestic and foreign tourists are quite high. The general evaluations were negative in terms of assurance. In terms of empathy, the evaluations of both domestic and foreign tourists are positive. In addition, the differences between the evaluations of domestic and foreign tourists on the quality of service in terms of their demographic characteristics were examined. The findings of the study will be used in the enterprises performing equestrian trekking activities so the visitors will be more satisfied with the services provided, the satisfaction level and consequently, the number of devoted customers will increase.